Rancang Bangun Aplikasi Presensi Dan Penggajian Karyawan Berbasis Mobile Pada CV. Maju Berkah Sosa Julu (Mabes-J) - Ibnu Sani Wijaya; Ihsan Nasution; Hendri Hendri; Dodi Sandra; Mulyadi Mulyadi (Sekawan Institut, 2025)
The attendance and payroll system currently implemented at CV. Maju Berkah Sosa Julu (Ma-bes-J) still uses a manual method or is still done by signing the attendance book. Every employee who comes to work is required to record their arrival time on the daily attendance sheet. The cri-teria for employee payroll is attendance, so the payroll system must be stricter in entering em-ployee attendance criteria, with slow and manual data processing also resulting in delays in sal-ary payments and the potential for miscalculation. As a result, not only employees are disadvan-taged, but also the company that has to bear the burden of employee dissatisfaction. The purpose of this study is to build a system that can increase employee productivity and satisfaction at CV. MABES-J. This application is expected to provide convenience for employees in recording at-tendance and providing clear information about the salary they receive. Researchers use the Agile method to develop the system, emphasizing flexibility and adaptation to change. The Agile ap-proach allows iterative system development, with a focus on collaboration and quick response to feedback. This study produces a system that brings significant changes in employee attendance management at CV. Maju Berkah Sosa Julu (Mabes-J). Before this system, the attendance record-ing process was done manually, which was often time-consuming and prone to errors. With the implementation of this new system, employees no longer need to fill in attendance manually. The system automatically records all attendance data, and integrates it into a centralized database.